Peran Kepuasan Kerja dalam Memediasi Pengaruh Lingkungan Kerja Non Fisik dan Work-Family Conflict terhadap Motivasi - Paladita, Ida Bagus; Cahyadi, Irwan; Yuliana, Ika; Faerrosa, Lady; Marlini, Febria Nurmelia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Employee motivation is essential in maintaining the productivity and performance of healthcare institutions, particularly in nursing services. However, motivation is often influenced by non-physical work environments and work-family conflict. This study aims to examine the effect of non-physical work environment and work-family conflict on motivation, with job satisfaction as a mediating variable. A quantitative associative approach was employed, involving 89 nurses from a public hospital in Lombok. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results revealed that both non-physical work environment and work-family conflict had a negative and insignificant effect on motivation. However, the non-physical work environment had a positive and significant effect on job satisfaction, while work-family conflict remained insignificant. Furthermore, job satisfaction demonstrated a positive and significant effect on motivation. The mediation analysis confirmed that job satisfaction successfully mediated the relationship between non-physical work environment and motivation but did not mediate the relationship between work-family conflict and motivation. These findings emphasize the central role of job satisfaction in enhancing employee motivation and suggest that creating a supportive non-physical work environment is more impactful than mitigating work-family conflict in the nursing context. This research contributes to organizational behaviour theory and offers practical recommendations for hospital management to improve internal work conditions that foster nurse motivation.